Prevalence of and risk factors for hypoglycemic symptoms after gastric bypass and sleeve gastrectomy. (10th April 2015) - Lee, Clare J.; Clark, Jeanne M.; Schweitzer, Michael; Magnuson, Thomas; Steele, Kimberley; Koerner, Olivia; Brown, Todd T.
<x xml:space="preserve">Abstract</x> Objective To determine the prevalence of and risk factors for postprandial hypoglycemic symptoms among bariatric surgery patients. Methods A questionnaire including the Edinburgh hypoglycemia scale was mailed to patients who underwent either Roux‐en‐Y gastric bypass (RYGB) or vertical sleeve gastrectomy (VSG) at a single center. Based on the questionnaire, the patients were categorized as having high or low suspicion for post surgical, postprandial hypoglycemic symptoms. Results Of the 1119 patients with valid addresses, 40.2% (N = 450) responded. Among the respondents, 34.2% had a high suspicion for symptoms of post bariatric surgery hypoglycemia. In multivariate analyses, in addition to female sex (P = 0.001), RYGB (P = 0.004), longer time since surgery (P = 0.013), and lack of diabetes (P = 0.040), the high suspicion group was more likely to report pre‐operative symptoms of hypoglycemia (P < 0.001), compared to the low suspicion group. Similar results were observed when the high suspicion group was restricted to those requiring assistance from others, syncope, seizure with severe symptoms, or medically confirmed hypoglycemia (N = 52). Conclusions One third of patients who underwent RYGB or VSG reported postprandial symptoms concerning for postsurgical hypoglycemia, which was related to the presence of pre‐operative hypoglycemic symptoms. Pre‐operative screening for hypoglycemic symptoms may identify a group of patients at increased risk of postbariatric surgery hypoglycemia.